LAND USE CONVERSION AND URBAN MOBILITY IN KANO METROPOLIS, KANO STATE, NIGERIA - YUSUF, AMINU; GWADABE, MOHAMMED; UKASHATU, ALI YAHAYA; ANAS, ABUBAKAR ABDURRAHMAN; MUHAMMAD, USMAN (Kashere Journal of Management Sciences, 2025)
This study investigates the impact of land use conversion on urban mobility in Kano metropolis, recognizing that the accelerating rate of urbanization is a globally acknowledged primary cause of residential land use change. This growth fuels a constant demand for land, leading to land conversion which carries significant environmental and developmental implications. The rapid urbanization, particularly in developing world cities like Kano, severely impacts the existing land use system, and unchecked conversion creates the potential for severe mobility problems when urban transport planning fails to keep pace. The study addresses a critical research gap by systematically analyzing the complex interplay of influencing factors at a local level. A cross-sectional survey design was employed to collect primary data using a structured interview schedule. The study area included eight Local Government Areas (LGAs) selected using purposive sampling: Municipal, Nassarawa, Fagge, Gwale, Tarauni, Dala, Ungogo, and Kumbotso. Data were analyzed using descriptive statistics and the Logit Regression Model. The results showed a statistically significant relationship between the independent variables and the dependent, with the model explaining 84% of the variation in the dependent variable. Specifically, the findings revealed that Land Area, Land Use Guide Plan, Road Functions, and Land Use in the Surrounding have a positive and significant effect on land use conversion in Kano Metropolis. The study concludes that these four variables are the main factors influencing land use conversion. It recommends enhancing community stakeholder engagement, integrating land use and transport planning, and strengthening and enforcing the land use guide plan.